Composing Concurrency Control - Ziv, Ofri; Aiken, Alex; Golan-Gueta, Guy; Ramalingam, G.; Sagiv, Mooly; Ramalingam, G. (Programming Language Design and Implementation, PLDI 2015, 2015)
Concurrency control poses significant challenges when composing computations over multiple data-structures (objects) with different concurrency-control implementations. We formalize the usually desired requirements (serializability, abort-safety, deadlock-safety, and opacity) as well as stronger versions of these properties that enable composition. We show how to compose protocols satisfying these properties so that the resulting combined protocol also satisfies these properties. Our approach generalizes well-known protocols (such as two-phase-locking and two-phase-commit) and leads to new protocols. We apply this theory to show how we can safely compose optimistic and pessimistic concurrency control. For example, we show how we can execute a transaction that accesses two objects, one controlled by an STM and another by locking.